A metric-based evaluation model for applications on mobile phone - Hussain, Azham; Kutar, Maria; Mohmad Kamal, Fazillah (2012)
Research on HCI, specifically on mobile application has started more than a decade. Usability metrics have been used as guidelines to evaluate the quality of the system as well as mobile applications. However, the metrics used for evaluation method keep changing due to the new inventions on mobile phones.Thus, there is a need to create a dynamic model for evaluation that can grow together with new inventions and technology.In this paper, we created a dynamic usability metrics model and test the model to ensure the model is reliable and effective.The model comprises usability goals, questions and metrics for evaluation of applications on mobile phone. This paper also reports the usability test results for applications installed on different mobile phone.